Comment on “Drug-Induced Lupus Following mRNA COVID-19 Vaccination and Monoclonal Antibody Infusion for Treatment of COVID-19 Infection” - daungsupawong, hinpetch; wiwanitkit, viroj (Kansas Journal of Medicine, 2024)
n/a